Strategi Manajemen dalam Mempercepat Kelayakan Klaim JKN/BPJS di Rumah Sakit Restu Ibu Balikpapan: Studi Kualitatif dengan Analisis SWOT - Tri Hardining Prawestirini; Erliany Syaodih; Mira Veranita (Pusat riset dan Inovasi Nasional, 2025)
Healthcare financing for patients covered by BPJS Kesehatan in hospitals is carried out through a claims mechanism. Delayed BPJS Kesehatan claims represent a critical issue within the healthcare service context in Indonesia. The aim of this study is to identify management strategies that can expedite the eligibility of BPJS Kesehatan claims at Restu Ibu Hospital in Balikpapan. This research is conducted using a descriptive qualitative approach, with data collection through interviews and Focus Group Discussions (FGD). The informants consisted of one doctor, three coders, and one verifier. The study begins by identifying the claim service system situation, focusing on both internal aspects (Strengths and Weaknesses) and external aspects (opportunities and Threats), also known as SWOT analysis. This study identifies several strategies, including: 1) Enhancing the competence of staff and medical personnel through regular training; 2) Developing a more advanced and integrated information system; 3) Improving communication with BPJS Kesehatan; 4) Improving documentation and data verification; and 5) Strengthening coordination with relevant units.